Associations between vitamin D metabolites, antiretroviral therapy and bone mineral density in people with HIV. Issue 5 (May 2016) - Klassen, K.; Kimlin, M.; Fairley, C.; Emery, S.; Anderson, P.; Ebeling, P.
Abstract Summary Rationale: To see if vitamin D and antiretroviral therapy are associated with bone mineral density (BMD) in people with HIV. Result: Lower hip BMD was associated with tenofovir (an antiretroviral medicine) in those with 25(OH)D ≥50 nmol/L. Significance: The relationship between antiretroviral therapy and hip BMD differs depending on vitamin D status. Introduction People with HIV have an increased risk of low BMD and fractures. Antiretroviral therapy contributes to this increased risk. The aim of this study was to evaluate associations between vitamin D metabolites and antiretroviral therapy on BMD. Methods The simplification of antiretroviral therapy with tenofovir-emtricitabine or abacavir-lamivudine trial (STEAL) was an open-label, prospective randomised non-inferiority study that compared simplification of current nucleoside reverse transcriptase inhibitors (NRTIs) to fixed-dose combination tenofovir-emtricitabine (TDF-FTC) or abacavir-lamivudine. Serum 25(OH)D and 1, 25(OH)2 D were measured in 160 individuals (90 receiving TDF-FTC, 70 receiving other NRTIs) at baseline from this study. Multivariable linear regression models were constructed to evaluate the covariates of 1, 25(OH)2 D and BMD. Results Protease inhibitor use (p = 0.02) and higher body mass index (BMI) (p = 0.002) were associated with lower 1, 25(OH)2 D levels in those with 25(OH)D <50 nmol/L. However, TDF-FTC use (p = 0.01) was associated with higher 1, 25(OH)2 D levels, but only in those with 25(OH)D ≥50 nmol/L. White ethnicity (p = 0.02) and lower BMI (p < 0.001) in those with 25(OH)D <50 nmol/L and with TDF-FTC use (p = 0.008) in those with 25(OH)D ≥50 nmol/L were associated with lower hip BMD. TDF-FTC use, higher serum calcium and serum βCTX, winter, and lower bone-specific alkaline phosphatase (BALP) and BMI were associated with lower lumbar spine BMD. Conclusion TDF-FTC use (versus non-TDF-FTC use) was associated with lower hip BMD, and this difference was more pronounced in those with 25(OH)D ≥50 nmol/L. Serum 25(OH)D <50 nmol/L was associated with lower hip BMD in all participants. Therefore, the associations between antiretroviral therapy and hip BMD differ depending on vitamin D status.